Investigating the influence of charge transport on the performance of PTB7:PC71BM based organic solar cells. Issue 25 (14th June 2018) - Chauhan, Mihirsinh; Sharma, Abhishek; Patel, Jessica; Aatif, M.; Chand, Suresh; Pandey, Manoj Kumar; Kumar, Manoj; Tiwari, J. P.; Tripathi, Brijesh
Abstract : The dependence of performance parameters on the incident power light intensity (IPL) and effective charge carrier mobility. Abstract : A key challenge for researchers in the field of organic solar cells (OSCs) is to develop a physical model for a device that correctly describes the charge carrier transport phenomenon. In this article, an analytical study on the charge carrier transport phenomenon in an OSC is reported, which expresses a balance between free charge carrier generation and recombination in low mobility PTB7:PC71 BM blend layers. First, the current density–voltage ( J – V ) data for the fabricated OSC were extracted from experiments by varying the incident power light intensity (IPL) and then analysis through theoretical simulation was used to quantify the dominant interface recombination parameters limiting the device's performance. It was found that although the generation of free charge carriers increased at higher IPL values, the performance of the device remained low due to poor electrical transport properties which resulted in a considerable accumulation of generated charge carriers in the active layer. Therefore, it has become important to work out the complex relation between charge carrier mobility, exciton-recombination dynamics and the overall electrical performance parameters in a single framework. This article explains the influence of incident power light intensity and charge carrier mobility on performance parameters, which limits the power conversion efficiency (PCE) of the OSC. The presented analysis could be helpful in optimizing the architecture of future devices to increase the PCE of OSCs.